Could free trade alleviate effects of climate change? A worldwide analysis with emphasis on Morocco and Turkey - Ismail Ouraich; Hasan Dudu; Wallace E. Tyner; Erol Cakmak (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper examines the interaction of globalization through trade liberalization and climate change, globally with a special focus on Morocco and Turkey. We use the GTAP model, which is a global general equilibrium model, to investigate trade liberalization welfare impacts under climate change, and its ability to provide mitigation and/or adaptation to potential losses. Our hypothesis was that trade liberalization would at least partially offset potential welfare losses induced by negative productivity shocks on agriculture. Our findings suggest that the world as a whole benefits the more trade is liberalized. For instance, under an unrealistic multilateral trade liberalization scenario, average net global welfare increases by +US76,676 million. Hence, initial average welfare loss under climate change, which reached -US31,775 million, is totally offset. Nonetheless, as we move away from complete trade liberalization to limited trade liberalization at the regional and sector levels, the gains realized are minimal and offset only marginally climateinduced welfare losses. At the regional level, most regions under trade liberalization do not experience large enough welfare gains to offset welfare losses triggered by negative productivity impacts in agriculture. The exceptions are countries/regions which are projected to benefit from climate change. For Morocco, tariff elimination under all scenarios on average induces additional welfare loss compared with the climate change only scenario. Despite the gains in allocative efficiency accruing from trade liberalization, the latter are generally low and are offset by the substantial negative contribution of the terms of trade and investment savings effects. For Turkey, trade liberalization induces net welfare gains under all scenarios. Nonetheless, these gains are not large enough to offset totally the initial loss under climate change. These results are primarily driven by the combined effect of allocative efficiency and terms of trade effects.
Keywords: F18; O13; O57; Q17; 330; climate change; adaptation; uncertainty; CGE model; trade liberalization